2011
DOI: 10.1063/1.3615846
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of electric field screening by the proximity of two knife-edge field emitters

Abstract: The electric field of two semi-infinitely wide knife-edge cathodes with arbitrary separation is calculated by using a Schwarz–Christoffel transformation. This geometry could also represent a trench (or scratch) on a flat surface. It is found that the magnitude of the electric field on the knife-edge cathodes depends strongly on the ratio h/a, where h is the height of the knife-edge cathodes and 2a is the distance between the cathodes. When h/a increases, the magnitude of the electric field on the cathode’s sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 30 publications
2
20
0
1
Order By: Relevance
“…Since E is edge centered, a bilinear interpolation is used to determine its value at the sharp corner. Therefore, the sharp corner is effectively being smoothed out, and the electric field at that location is no longer infinite as theoretical analysis predicted, 11,21 and the current densities at the sharp corner become finite and integrable. In order to determine b eff as a function of the applied voltage, we employed the following procedure.…”
Section: Theory and Modelingmentioning
confidence: 94%
See 1 more Smart Citation
“…Since E is edge centered, a bilinear interpolation is used to determine its value at the sharp corner. Therefore, the sharp corner is effectively being smoothed out, and the electric field at that location is no longer infinite as theoretical analysis predicted, 11,21 and the current densities at the sharp corner become finite and integrable. In order to determine b eff as a function of the applied voltage, we employed the following procedure.…”
Section: Theory and Modelingmentioning
confidence: 94%
“…[6][7][8][9][10][11] Recently, we studied analytically the electric field screening of two semi-infinitely wide knifeedge cathodes with arbitrary separation by using conformal mapping and showed that the magnitude of the electric field on the knife-edge cathodes depends strongly on the aspect ratio h/a, where h is the height of the cathodes and 2a is the distance between the cathodes. 11 For experimental works, Nilsson et al reported that the emitted current density can be optimized by tuning the density of the carbon nanotubes (CNTs) on a film. 9 Later, Suh et al studied the field screening effect due to the proximity of neighboring CNTs by changing the height of the carbon nanotubes fabricated on porous anodic aluminum oxide templates.…”
Section: Introductionmentioning
confidence: 99%
“…The cathode is negatively biased by using a computer controlled FX30N10 power supply, and in series with a 30 kΩ limiting resistor to reduce the effects of over-current on the power supply. 13,14,20 In situ diagnostics consist of a voltage divider providing voltage measurements across the A-K gap, and a current viewing resistor (CVR) for measuring the cathode current. We control the cathode current and voltage using the Lab Assistant 1.0 software package, developed by CCT, Inc., which also serves as the data acquisition software.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, in previous work, we explored the emission characteristics of two-and four-fiber arrays of carbon emitters in a carefully prepared, simple geometry. [13][14][15][16][17][18][19] Our configuration allows a much more pristine and straightforward experimental geometry for isolating and interpreting the electric field screening from other effects such as work function variation across the cathode surface or statistical inhomogeneities in the geometry of the individual emitters that comprise the array.…”
Section: Introductionmentioning
confidence: 99%
“…Electric field screening by the proximity of neighboring emitters is found to have a profound effect on the field enhancement factor of the cathode. [18][19][20] Recently, it is shown that field enhancement factor strongly depends on the finite anode-cathode gap distance when the emitter tip-to-anode distance is comparable to or smaller than the emitter height. 8 In this paper, we study the FE characteristics of a CNT fiber emitter in different anode-cathode (AK) gap distances.…”
mentioning
confidence: 99%